Advanced Unruptured Cornual Pregnancy - mariye, yitbarek Fantahun; tesfaye, kiflom; hassen, salih (Ethiopian Journal of Reproductive Health, 2020)
Ectopic pregnancy is one of the major causes of maternal morbidity and mortality. Cornual pregnancy is a rare type of ectopic pregnancy where the gestational sac is implanted in the cornua part of the tube, it’s more dangerous than other types of ectopic pregnancies, and contributes a significant amount of maternal mortality and morbidity. Here a case report is presented where a patient was admitted to a rural hospital and with a diagnosis of missed abortion. Total of 2000 µg of Misoprostol given and repeated two times and later referred where laparatomy was done after the diagnosis was made by transvaginal ultrasound. Key word: Cornual pregnancy, unruptured ectopic, Ectopic pregnancy